An Investigation on Seismically Isolated Buildings in Near-Fault Region - Sesli, Hasan; Tonyalı, Zeliha; Yurdakul, Muhammet (İdris Karagöz, 2022)
In this study, the effects of far-fault, near-fault and pulse-type ground motions on a seismically isolated building were investigated. The 3-dimensional finite element model of the building was created in the SAP2000 software and the dynamic characteristics were determined numerically. Three different earthquake ground motion characteristics of 1999 Düzce Earthquake in Turkey were selected to evaluate the structural behavior. The record motions of the Mudurnu and Sakarya station were selected as far-fault ground motion. For near-fault ground motion, 1999 Düzce Earthquake Düzce and Lamont 1062 station records were selected. 1999 Düzce Earthquake Bolu and IRIGM 487 station records were selected as pulse-type ground motion. The behavior of the building supported by friction pendulum isolators with a displacement capacity of 48 cm was compared with the analysis results of fixed-base building. The displacement values of the 1st, 4th and 7th floors of the building were obtained. The effects of earthquake ground motions and isolator were evaluated according to floor displacement values. The seismically isolated building has a less structural demand depending on the vibration mode period under pulse-like near-fault ground motions.
Keywords: Reinforced Concrete Buildings; Betonarme Yapılar